Soil water samples from the drained thaw lake basin near Barrow, Alaska, used for the Biocomplexity Experiment, 2009 ... - Lipson, D.; Oechel, W. (NSF Arctic Data Center, 2013)
In 2009, soil water samples were collected from the drained thaw lake basin used for the Biocomplexity Experiment, near Barrow, Alaska (AK). The northern section of the basin was experimentally flooded. Samples were collected from 0-5 and 5-15 cm depths using Rhizon soil moisture samplers and analyzed for dissolved iron-Fe, organic carbon-C, ultraviolet-UV absorbance at 280nm, ammonium, nitrate, amino N, and phosphate. See Lipson et al. (2012) Biogeosciences 9:1-15. ...